Patterns of adherence to home blood pressure monitoring among men and women in the Electronic Framingham Heart Study - Tenes J. Paul; Katherine Sadaniantz; Apurv Soni; Jean-Claude Asaker; Chathurangi H. Pathiravasan; Jordy Mehawej; Andreas Filippaios; Yuankai Zhang; Ziyue Wang; Chunyu Liu; Honghuang Lin; Joanne M. Murabito; et al. (PLoS ONE, 2025)
Worldwide, there are differences in hypertension control by sex. The use of home blood pressure monitoring (HBPM) is associated with lower average blood pressures and higher medication adherence. However, little is known about adherence trajectories and sex differences in HBPM. This study characterizes adherence to HBPM among those with and without hypertension. Electronic Framingham Heart Study participants were instructed to perform HBPM weekly for 1 year. Adherence was defined as having ≥1 measurement per week averaged over 4-week segments. Primary exposures of hypertension status and sex were self-reported. Group-based trajectory modeling was used to identify adherence trajectories. Logistic regression was applied to investigate factors associated with membership in each trajectory group in the sex-stratified and whole cohorts. Among 990 participants (58% women, age 53 ± 9 years, 26% hypertension), three groups with distinct HBPM adherence patterns were identified: “early discontinuation”, “gradual decrease”, and “high adherence”. Participants with hypertension were more likely to maintain “high adherence” compared to those without (OR 1.55; 95% CI 1.08–2.23), with similar findings seen among women with hypertension (OR 2.24; 95% CI 1.35–3.72) but not men. In women, these findings remained significant when adjusting for anxiety, depression, and blood pressure, but were attenuated by adjusting for age and income. This study highlights HBPM adherence trajectories and shows that women with hypertension were more likely to be in the high adherence group, though these associations were attenuated after adjusting for demographic factors and co-morbidities. Future studies should explore strategies to enhance adherence in populations at risk of early discontinuation.